Efforts to Increase Legal Awareness on Violent Behavior by Ende Residents in Surabaya City - Retno Dewi Pulung Sari; Nany Suryawati (Universitas Muhammadiyah Sidoarjo, 2023)
The legal system which is based on and inspired by the philosophical values of Pancasila, aims to improve the legal system in Indonesia. That is able to protect its citizens from all actions or behaviors that are contrary to humanity and justice. Therefore, Indonesian law contains elements of protecting implementing order, justice, and especially non-discrimination, especially from gender. The law creates a dignified society, which humanizes humans, upholds human values. The norms that live in society, become a basis for the formation of a rule. But the customs and habits that exist in ethnic groups in Indonesia have their own character. Violence cannot be identified in a particular society, but all humans can have a hard character. However, the existence of a belis or dowry, seems to give legitimacy that women have been bought. Therefore, through this community service activity, it focuses focuses on efforts to increase awereness of the law in the hope of minimizing the habit of violent behavior in the nomad community from Ende in the Surabaya city. This effort to increase awereness of the law is carried out through legal assistance regarding domestic violence in the Ende nomad community in Surabaya City. The assistance of representatives of Ende residents in Surabaya related to Law Number 23 of 2004 concerning Domestic Violence needs to be carried out intensively and massively. There is a decrease in the level of domestic violence in the families of Ende nomads in Surabaya. Highlights: Legal System Based on Pancasila: The legal system in Indonesia is inspired by the philosophical values of Pancasila, aiming to protect citizens and uphold humanity, justice, and non-discrimination, especially concerning gender. Focus on Awareness and Minimizing Violence: Community service activity focuses on increasing awareness of the law to minimize violent behavior within the nomad community from Ende in Surabaya. Intensive Legal Assistance: Representatives of the Ende residents in Surabaya provide intensive and massive legal assistance related to Law Number 23 of 2004 concerning Domestic Violence, resulting in a decrease in domestic violence in the Ende nomad families. Keywords: Violent Behaviour, Belis Culture, Legal Awereness, Domestic Violence, Nomad Community